PENGARUH PENGGANTIAN SEBAGIAN RANSUM DENGAN TEPUNG LIMBAH LABU KUNING (Cucurbita moschata) TERHADAP PERFORMANS AYAM PEDAGING - Salauhiang, Julin; Najoan, Marie; Pontoh, Cherly J.; Imbar, Meity R. (ZOOTEC, 2019)
EFFECT OF REPLACEMENT SOME RATIONS WITH FLOUR YELLOW PUMPKIN WASTE (CUCURBITA MOSCHATA) AGAINST PERFORMANCE BROILER. This study aims to determine   the extent of the partial replacement of rations with pumpkin waste flour (Cucurbita moschata) as measured by broiler performance. Using 100 unsexed broiler Cobb 707 aged 1 day with average body weight ± 45.32 g. The design used was a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications. The treatment composition is as follows: R0 = 100% basal ration (RB) + 0% pumpkin waste flour (TLLK), R1 = 95% RB + 5% TLLK, R2 = 90% RB + 10% TLLK, R3 = 85% RB + 15% TLLK.  Results of analysis of variance showed that the dissecting treatment was not significant (P>0.05) for the consumption, weight and conversion of ration The use of pumpkin waste flour can replace a portion of the ration up to 15%.Key words: Performance, waste pumpkin, broiler.